Nonlinear optical responses of phthalocyanines in the presence of nanomaterials or when embedded in polymeric materials - Bankole, Owolabi Mutolib (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2017)
This work describes the synthesis, photophysical and nonlinear optical characterizations of alkynyl Pcs (1, 2, 3, 8 and 9), 1,2,3-triazole ZnPc (4), mercaptopyridine Pcs (5, 6 and 7) and amino Pcs (10 and 11). Complexes 1, 2, 4, 7, 8, 9 and 11 were newly synthesized and characterized using techniques including 1H-NMR, MALDI-TOF, UV-visible spectrophotometry, FTIR and elemental analysis. The results of the characterizations were in good agreement with their molecular structures, and confirmed the purity of the new molecules. Complex 10 was covalently linked to pristine graphene (GQDs), nitrogen- doped (NGQDs), and sulfur-nitrogen co-doped (SNGQDs) graphene quantum dots; gold nanoparticles (AuNPs); poly(acrylic acid) (PAA); Fe3O4@Ag core-shell and Fe3O4- Ag hybrid nanoparticles via covalent bonding. Complex 11 was linked to Agx Auy alloy nanoparticles via NH2-Au and/or Au-S bonding, 2 and 3 were linked to gold nanoparticles (AuNPs) via clicked reactions. Evidence of successful conjugation of 2, 3, 10 and 11 to nanomaterials was revealed within the UV-vis, EDS, TEM, XRD and XPS spectra. Optical limiting (OL) responses of the samples were evaluated using open aperture Z-scan technique at 532 nm and 10 ns radiation in solution or when embedded in polymer mixtures. The analyses of the Z-scan data for the studied samples did fit to a two-photon absorption mechanism (2PA), but the Pcs and Pc-nanomaterial or polymer composites also possess the multi-photon absorption mechanisms aided by the triplet-triplet population to have reverse saturable absorption (RSA) occur. Phthalocyanines doped in polymer matrices showed larger nonlinear absorption coefficients (ßeff), third-order susceptibility (Im [x(3)]) and second-order hyperpolarizability (y), with an accompanying low intensity threshold (Ium) than in solution. Aggregation in DMSO negatively affected NLO behaviour of Pcs (8 as a case study) at low laser power, and improved at relatively higher laser power. Heavy atom-substituted Pcs (6) enhanced NLO and OL properties than lighter atoms such as 5 and 7. Direct relationship between enhanced photophysical properties and nonlinear effects favoured by excited triplet absorption of the 2, 3, 10 and 11 in presence of nanomaterials was established. Major factor responsible for the enhanced nonlinearities of 10 in the presence of NGQDs and SNGQDs were fully described and attributed to the surface defects caused by the presence of heteroatoms such as nitrogen and sulfur. The studies showed that phthalocyanines-nanomaterial composites were useful in applications such as optical switching, pulse compressor and laser pulse narrowing.
Keywords: Phthalocyanines; Phthalocyanines -- Optical properties; Alkynes; Triazoles; Nonlinear optics; Photochemistry; Complex compounds; Amines; Mercaptopyridine